The role of electrodeposition current density in the synthesis and non-enzymatic glucose sensing of oxidized zinc-tin hybrid nanostructures. (April 2020) - Khan, Shakil; Rasheed, Muhammad Asim; Waheed, Abdul; Shah, Attaullah; Mahmood, Arshad; Ali, Tahir; Nisar, Amjad; Ahmad, Mashkoor; Karim, Shafqat; Ali, Ghafar
Abstract: This work reports the synthesis of different zinc-tin oxidized hybrid nanostructures and their non-enzymatic glucose sensing performance. Co-deposition of metallic Zn and Sn has been performed on copper (Cu) substrates at different current densities (15, 20, 25 & 30 mA/cm 2 ). The electrodeposited Zn–Sn films have been hydrothermally treated at 95 °C for 12 h to obtain oxidized Zn–Sn hybrid nanostructures. XRD data confirmed the formation of zinc oxide (ZnO) and tin oxide (SnO2 and SnO) without exhibiting metallic phases. The FE-SEM and EDX results reveal that the current density is the controlling factor for surface morphology and Sn content (from 4 at% to 16 at%), respectively. Photoluminescence spectra also show that UV impurity peak intensity is enhanced with the increase in current density due to the rise in tin oxide content. The potential of oxidized Zn–Sn nanostructures have been explored for the non-enzymatic glucose sensing using electrochemical methods like cyclic voltammetry (CV) and amperometry. The response time of about 1 sec was observed for all the modified electrodes. The non-enzymatic glucose sensing performance for oxidized Zn–Sn electrodes is found to be strongly dependent on tin content and surface morphology. A higher glucose detection sensitivity of 2135 μA mM −1 cm −2 (in the range of 0.5 μM–0.1 mM) has been observed for oxidized Zn–Sn electrode prepared at 30 mA/cm 2 . This study demonstrates the potential of oxidized Zn–Sn hybrid nanostructures toward non-enzymatic glucose sensing.